Isolation and identification of flavonoids from Tetracera indica Merr. (Dilleniaceae) leaves - Ahmed, Qamar Uddin; Alhassan, MA; Hasan, Md. Mahmudul (Stu); Khatib, Alfi; Sarian, Murni Nazira; Latip, Jalifah (2016)
Leaves of Tetracera indica are used in traditional medicine for the treatment of diabetes mellitus in Malaysia. This study was aimed at investigating the phytochemical constituents present in T. indica leaves which may be responsible for the antidiabetic effect of the plant’s leaves. Crude methanolic extract from the leaves of T. indica was separated and purified by column chromatography of silica gel, ODS and sephadex LH-20. The structures of the isolated compounds were identified and elucidated by UV, 1H-NMR, 13C-NMR and MS spectroscopic techniques. Four flavonoids were isolated from the leaves of T. indica, and these compounds were identified as follows: 5,7-dihydroxy-8-methoxyflavone (wogonin), 5,7,8-trihydroxyflavone (norwogonin), quercetin and 5-Hydroxy-7-methoxyflavone (tectochrysin). The three compounds i.e. norwogonin, quercetin and tectochrysin are being reported for the first time from T. indica leaves. Keywords: Tetracera indica, flavonoids, diabetes mellitus